On the discovery of tetrapod trackways from Permo-Carboniferous redbeds of Prince Edward Island and their biostratigraphic signiﬁcance - Calder, John; Baird, Donald; Urdang, Elliott (Atlantic Geology, 2004)
ABSTRACT The ﬁrst fossil tetrapod footprints that were discovered on Prince Edward Island, and which were previously undescribed, are small reptilian trackways assignable to the ichnogenera Notalacerta andGilmoreichnus. Their closest zoological correlatives are small, Permo-Carboniferous "stem-reptiles" of the families Protorothyrididae and Captorhinidae in the suborder Captorhinomorpha, and pelycosauran reptiles, possibly of the Ophiacodontidae. Reptiles of this type are rare to unrepresented in the skeletal fauna of the province. The biochronology of the track-bearing bed, combined with terrestrial vertebrate, palynological and macroﬂoral records, suggest that the host Pictou Group redbeds on Prince Edward Island young from late Stephanian (Pennsylvanian) at Malpeque Bay to early Permian in the north. The combined discoveries of tetrapod footprints and trackways from these Permo-Carboniferous redbeds suggests that the record is potentially extensive. Now included in this record is the youngest known occurrence of the ichno-genusNotalacerta.